Antibiotics and antivirals for dementia and mild cognitive impairment - Zhou, Yan (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The objective of this review is to evaluate the efficacy and adverse effects of antibiotics (except D‐cycloserine) and antiviral agents for dementia and mild cognitive impairment.